2000
DOI: 10.1021/es991047r
|View full text |Cite
|
Sign up to set email alerts
|

Tracing the Sources of PCDD/Fs and PCBs to Lake Baikal

Abstract: Lake Baikal is a unique freshwater ecosystem that has been declared a UNESCO World Heritage Site. It contains high levels of PCBs, and Baikal seal were recently found to have PCDD/F concentrations comparable to those in the Baltic Sea. In this work fish and soil were analyzed to trace the sources of these compounds to the lake. The fish samples indicated that the PCDD/F and PCB contamination of Lake Baikal does not originate from background inputs and that the contamination increases from north to south. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 18 publications
1
32
0
Order By: Relevance
“…This site was an urban city within 300 m from an MSWI, and several small factories were located nearby. The sampling times and total collected air volumes were ~24 hr and 1000-1300 m 3 , respectively. The sample information is presented in Table 1.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This site was an urban city within 300 m from an MSWI, and several small factories were located nearby. The sampling times and total collected air volumes were ~24 hr and 1000-1300 m 3 , respectively. The sample information is presented in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…The identification of the contamination source for an impacted area is necessary before steps can be taken to reduce the emissions and proceed with remedial action. To trace the source of contamination, a comparison of the PCDD/F homologue patterns in environmental samples with those in source emissions is made either by a simple direct comparison [1][2][3] or by using statistical methods such as principal component analysis (PCA) and cluster analysis. [4][5][6][7][8][9] The determination of characteristic homologue patterns in representative environmental samples is essential to evaluate the relationship between sources and impacted areas.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of all, the OCDD level was the lowest. PCDF levels were higher than those of PCDDs, and many studies have reported the same conclusions among the various thermal processes in flue gases (Lohmann and Jones, 1998;Oh et al, 1999;Mamontov et al, 2000). The homologue patterns found in the air samples were different from those found in stack gas.…”
Section: Comparison Of Homologue Patterns In Air Soil and Stack Gas mentioning
confidence: 82%
“…The highest concentrations of these particles which originate from coal-burning factories were found in the southern basin of the lake (Flower, 1998;Rose et al, 1998). Atmospheric pollution may also be responsible for the PCB and PCDD contamination of the lake, which increases from north to south (Mamontov et al, 2000). …”
Section: Atmospheric Pollutionmentioning
confidence: 99%